2015
DOI: 10.6061/clinics/2015(11)06
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of adenoviral conjunctivitis at the Clinical Hospital of the State University of Campinas, Brazil

Abstract: OBJECTIVES:Viral conjunctivitis is a common, highly contagious disease that is often caused by an adenovirus. The aim of this study was to evaluate the prevalence of adenoviral conjunctivitis by analyzing data from a prospective clinical study of 122 consecutively enrolled patients who were treated at the Clinical Hospital of the State University of Campinas (UNICAMP) after a clinical diagnosis of infectious conjunctivitis between November 2011 and June 2012.METHODS:Polymerase chain reaction was used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Viruses are associated with up to 80% of all prevalence of acute conjunctivitis 16-20 . 65 to 90% of cases of viral conjunctivitis are caused by adenoviruses, and it produces two common clinical symptoms related to viral conjunctivitis: pharyngoconjunctival fever (high fever, pharyngitis and bilateral conjunctivitis) and keratoconjunctivitis (lymphadenopathy). In another report from Southeastern Brazil, in Sao Paulo, the authors found a prevalence of 59.0% with acute conjunctivitis associated with adenovirus diagnosed by PCR 21 . In addition, in Northeastern Brazil, in Fortaleza, a study assessing 24 patients demonstrated that 12 (50%) tested positively for viral infection 22 .…”
Section: ■ Discussionmentioning
confidence: 92%
“…Viruses are associated with up to 80% of all prevalence of acute conjunctivitis 16-20 . 65 to 90% of cases of viral conjunctivitis are caused by adenoviruses, and it produces two common clinical symptoms related to viral conjunctivitis: pharyngoconjunctival fever (high fever, pharyngitis and bilateral conjunctivitis) and keratoconjunctivitis (lymphadenopathy). In another report from Southeastern Brazil, in Sao Paulo, the authors found a prevalence of 59.0% with acute conjunctivitis associated with adenovirus diagnosed by PCR 21 . In addition, in Northeastern Brazil, in Fortaleza, a study assessing 24 patients demonstrated that 12 (50%) tested positively for viral infection 22 .…”
Section: ■ Discussionmentioning
confidence: 92%
“…Less common causes include herpetic viruses, picornaviruses, Epstein-Barr virus, influenza viruses, paramyxovirus and poxviruses. Results from studies conducted in Brazil showed that adenoviruses were involved in 59% of all viral cases of conjunctivitis in that country 26 , whereas worldwide, adenoviruses have been found to be involved in 15% to 70% of all cases of infectious conjunctivitis…”
Section: IIImentioning
confidence: 99%
“…In recent years, viral conjunctivitis is the most common, followed by bacterial conjunctivitis [3,4], and adenovirus is one of the main causes of viral conjunctivitis. Human adenoviruses (HAdV) are non-enveloped, a doublestranded DNA virus [5][6][7][8][9][10][11] with icosahedral capsids in the family Adenoviridae. The viral particles roughly 65 to 80nm in size consist of protein capsid, core protein and DNA.…”
Section: Introductionmentioning
confidence: 99%